Investigation of Amounts of Vitamins, Lycopene, and Elements in the Fruits ofOpuntia ficus-indicaSubjected to Different Pretreatments - Bakar, Busra; Cakmak, Meltem; Ibrahim, Muhammad Salihu; Ozer, Dursun; Saydam, Sinan; Karatas, Fikret (Springernature, 2020)
In this study, Opuntia ficus-indicafruit was examined in fresh, frozen, sun-dried, and microwave-dried. Analysis of the vitamins in the samples was performed by high performance liquid chromatography (HPLC). The amount of selenium in the fruits was determined by fluorescence spectrophotometer, while copper, iron, manganese, and zinc were determined by atomic absorption spectrophotometer (AAS). Amount of vitamins in the fruit ofOpuntia ficus-indicawere decreased (p < 0.005) in sun- and microwave-dried samples in comparison with fresh sample. Decrease of vitamins in frozen fruits was statistically insignificant compared with fresh fruit (p > 0.05). The amounts of selenium, copper, iron, manganese, and zinc inOpuntia ficus-indicafruit were found to be 0.38 +/- 0.03, 23.84 +/- 1.82, 94.32 +/- 7.04, 13.68 +/- 0.88, and 188.44 +/- 15.16 mu g/g dw, respectively. It can be concluded that the fruit ofOpuntia ficus-indicais rich in vitamin E, lycopene, ascorbic acid, nicotine amide, folic acid, iron, and zinc. The most suitable preservation techniques forOpuntia ficus-indicafruits are freezing to consume it in all season.
Keywords: Opuntia ficus-indica; Frozen; Sun-and microwave-dried; Vitamins; Lycopene; Elements